EFFECT OF DIFFERENT MATERIALS ON FOAM PADS USED IN MODIFIED CLINICAL TEST OF SENSORY INTERACTION ON BALANCE (MCTSIB) FOR BALANCE IN INDIVIDUALS WITH VESTIBULAR DYSFUNCTION. - Dr. Swejal Gajbhiye,Dr. Amruta Doijad (Cuestiones de Fisioterapia, 2025)
Introduction Vestibular dysfunction affects a significant number of individuals, leading to dizziness and balance impairment. Population studies indicate that approximately 1.6% of individuals experience peripheral vestibular disorders. The Modified Clinical Test of Sensory Interaction on Balance (mCTSIB) is widely used to assess a patient’s dependence on sensory inputs for balance and to customize rehabilitation strategies accordingly.